COMMUNICATION STRATEGIES FOR HINDU RELIGIOUS COUNSELING IN DENPASAR CITY - Ni Gusti Ayu Kartika; Dewa Ayu Putu Tuty Setiarsih (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
Communication strategy is an essential aspect of Hindu religious counseling in Denpasar City. However, communication in Hindu religious counseling in Denpasar City often faces challenges due to the heterogeneity and diverse cultural characteristics of the counseling audience. Therefore, this study aims to analyze the communication strategies of Hindu religious counselors under the Ministry of Religious Affairs in Denpasar City, focusing on the planning, implementation, and implications of communication strategies in Hindu religious counseling. These three aspects are analyzed using the S-M-C-R communication model and the S-O-R theory. This research employs a qualitative method with a phenomenological approach. Data collection methods include observation, interviews, documentation, and literature study. The study results indicate that the planning of communication strategies in Hindu religious counseling revolves around key communication elements: the Hindu religious counselor as the source, the message delivered, the communication channel, the recipient, and the effect (response). The implementation of communication strategies in Hindu religious counseling in the field involves several key steps, such as preparing comprehensive materials before delivering the counseling, conveying the material clearly and accurately to the community, and providing justification and evaluation of the counseling materials presented.